Microwave assisted green chemistry approach of sodium metaborate dihydrate (NaBO2•2H2O) synthesis and use as raw material for sodium borohydride (NaBH4) thermochemical production - Figen, Aysel Kanturk; Piskin, Sabriye (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In the present study, a novel microwave assisted method has been developed for sodium metaborate dihydrate (NaBO2 center dot 2H(2)O) synthesis. Anhydrous NaBO2, a derivative of borax, is an industrially and technologically important boron compound used as a raw material for the thermochemical production of sodium borohydride (NaBH4). The effects of different microwave treatment conditions such as microwave power (90, 270 and 360 W) and irradiation time (1, 2, and 5 min) on the synthesis of NaBO2 center dot 2H(2)O were examined. After microwave irradiation at 270 W for 1 min, NaBO2 crystals with 2 molar equivalents of water were formed. Anhydrous NaBO2 was obtained following incubation at 400 degrees C for 33 min under calcination conditions. Then the resulting anhydrous NaBO2 powder was reacted with MgH2 under 60 bar hydrogen atmosphere at 470 degrees C, leading to successful production of NaBH4 with 93% yield. Copyright (C) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Sodium metaborate; Microwave; Sodium borohydride; Thermochemical; Hydrogen storage; MAGNESIUM; BORATE; NABO2; Chemistry; Electrochemistry; Energy & Fuels